Epidemiological analysis and biological mechanisms associated with periodontitis and obesity during pregnancy: systematic review and meta-analysis combined with clinical studies based on Omics techniques - Júnior, Gerson Aparecido Foratori (2023)
This study aimed to (1) assess the association between overweight and periodontitis during pregnancy through systematic review and meta-analysis (SR+MA); (2) elucidate the metabolomic profile of saliva and plasma associated with obesity and periodontitis during pregnancy; (3) compare the metabolic profile of unstimulated (US) and stimulated (SS) saliva samples from pregnant women with/without obesity and periodontitis; (4) analyze salivary proteomics related to obesity and periodontitis in women during pregnancy (T1) and after delivery (T2); and (5) compare the proteomic profile of US and SS from pregnant women with/without obesity and periodontitis. Regarding SR+MA, EMBASE, SCOPUS, PubMed/MEDLINE, Web of Science, BVS/LILACS, Cochrane Library and SCIELO were accessed. The Newcastle-Ottawa scale was used to assess the risk of study bias. Most studies had a low risk of bias. A positive association between overweight/obesity and periodontitis was found (RR 2.21; 95% CI 1.533.17; p < 0.001). For the clinical studies, 126 women were recruited and, after exclusions, they were allocated into groups: obesity+periodontitis (OP); obesity/no periodontitis (OWP); normal BMI+periodontitis (NP); normal BMI/no periodontitis (NWP). Saliva and plasma samples were collected to analyze the metabolomic profile using Proton Nuclear Magnetic Resonance (1H-NMR). Proteins were extracted from the saliva samples and individually processed by label-free proteomics (nLC-ESI-MS/MS). In metabolomics, plasma analysis indicated that glucose (p=0.041) and phenylalanine (p=0.015) levels were positively correlated with periodontal parameters and BMI, respectively. In saliva, periodontitis was mainly associated with high levels of acetic acid (p=0.024), isovaleric acid, butyric acid, leucine, valine, isoleucine and propionic acid (p<0.001). High salivary concentrations of glycine (p=0.015), succinic acid (p=0.015) and lactate (p=0.026) were associated with obesity. Metabolites in elevated concentration in US samples compared to SS were 5-Aminopentoate, Acetic acid, Butyric acid, Propionic acid, Pyruvic acid, and Succinic acid. In proteomics, the Heat Shock Proteins 70 kDa 1A, 1B and 1-like were upregulated and were related to obesity and periodontitis separately. Albumin and Thioredoxin were upregulated in cases of periodontitis, while cystatins (mainly S, SA, SN) and Lactotransferrin were downregulated. High abundances of Submaxillary gland androgen-regulated protein 3B, Protein S100-A8, Matrix metalloproteinase 9, Heat shock 70 kDa protein 2 and 6, Putative Heat shock 70 kDa protein 7, Heat shock 71 kDa protein, Haptoglobin and Plastin-1 were significant for those with obesity and periodontitis together. Substantial alterations in proteomic profile were identified after delivery. Proteins involved with immune response process, antioxidant activity, and retina homeostasis were decreased or absent in SS samples from all groups. In conclusion, a positive association was found between overweight/obesity and periodontitis during pregnancy according to SR+MA. Furthermore, saliva demonstrated a more enlightening difference than plasma for the analysis of metabolites, indicating the glucosealanine cycle, alanine metabolism, degradation of valine, leucine and isoleucine, glutamate metabolism and the Warburg effect as the main metabolic pathways. Also, obesity and periodontitis remarkably altered the salivary proteome during pregnancy with substantial alterations after delivery. Finally, there are significant differences in the metabolomic and proteomic profiles of unstimulated and stimulated saliva samples from pregnant women with/without obesity and periodontitis.